STRENGTHENING BRAWIJAYA UNIVERSITY’S SUSTAINABILITY STRATEGY THROUGH SDGs INTEGRATION IN SUSTAINABILITY REPORT - IKA MAKHERTA SUTADJI; Eko Ganis Sukoharsono; Lilik Purwanti; Endang Mardiati; Khairul Shaleh (Universitas Widyatama, 2025)
The goal of this research is to examine the extent to which Universitas Brawijaya (UB) discloses its contribution in its Sustainability Report to the Sustainable Development Goals (SDGs). The content analysis methods employed in this qualitative investigation are based on the Global Reporting Initiative (GRI Standards 2021) and the SDG Compass framework. The data used are derived from UB's 2022 sustainability report. The sustainability of disclosures and their role in accomplishing the SDGs were evaluated through content analysis. The study results indicate that UB received a Gold Award from the Asia Sustainability Reporting Rating (ASRRAT) 2022. This study found that the integration of SDGs in UB's sustainability report is still partial, predominantly focused on descriptive aspects of activities and not fully impact-based reporting. Policy recommendations include strengthening the integration of SDGs into university governance, enhancing the caliber and openness, developing academically based sustainable innovation, and expanding cross-sector strategic partnerships. Furthermore, a formal stakeholder-based materiality assessment is needed as a concrete action. These findings contribute to strengthening Universities' function as change agents in Indonesia's sustainable development.